Notas sobre o debate entre a modernidade e a tradição nas ideias pedagógicas nas décadas de 1920 e 1930: o esboço de um conflito - Baldan, Merilin (2015)
The PhD research with the title Highlighting the debate between tradition and modernity in pedagogical ideas during the 1920-1930 decades: the sketch of a conflict is an investigation about pedagogical press and pedagogical ideas. The main source of this research is the Serie Atualidades Pedagógicas, linked to the Collection Biblioteca Pedagógica Brasileira, edited by Fernando de Azevedo, one of the leaders of Brazilian Progressive Education Movements. We delineate the sources over the period from 1931 to 1939 in which the Serie had published the majority of titles linked to Biology and Psychology Sciences, due to the projections of these sciences for innovation of Education by Progressive Education Movements. The research question can be describe in the next questions: How did the aspects of tradition and modernity constituted the pedagogical ideas in Progressive Education Movement in Brazil? What is the contribution of Biology and Psychology in the discussion about the old and new in Education among the titles published in the Serie Atualidades Pedagógicas? . The main aim is to apprehend and analyse the relation between tradition and modernity in the clash of the pedagogical ideas in the first part of the XXth century from the analysis corpus. The specific objectives can be described as in the next points: (a) Comprehend the clash between the tradition and modernity in the Azevedo Pattern in the Serie Atualidades Pedagógicas (1931 to 1939); and, (b) Reveal the contributions of Biological and Psychological Sciences to innovate the pedagogical ideas, considering the concepts of school, teacher and children. The theoretical framework to support our analysis is based on the Cultural History, highlighted theories by Marc Depaepe and Michel de Certeau. The doctoral research was organized in introduction, three chapters and conclusion. The first chapter has the main aim to discuss the theoretical framework used in our source s analysis. The second chapter has the main objective to present the historical, social, economical and cultural context in which is developed the society, the education and Fernando de Azevedo s reforms and his educational discourse. The historical time let us observe a double relationship between social-cultural and educational aspects in concern with the modernization of society and educational reform among the politics, intellectuals and educators in this time. The Azevedo´s viewpoint as journalist, reformer, editor and intellectual let us to comprehend the ways as him organize the titles and authors to compose his Series Atualidades Pedagógicas. The third chapter has the objective to point out the homogeneous and heterogeneous ideas from Progressive Education Movement, the role of Biology and Psychology in the educational thought and analysis of the sources from analytical categories: school s, teacher s and children s conception. In this sense, we can observe that some questions, in circulation during this time, it were common and result in a homogenous ideas among the pedagogical discourse. However, these ideas, representing different ways to interpret, translate, appropriate and uses in the educational field, that is, heterogeneous ideas. The build and development of the sciences occurred pari passu with the appropriations and results in a vary among the scientific filed. The biological and psychological sciences conducted to discovery and review of child´s, teacher´s and school´s concepts. In summ, it is important to observe the demithyfication of intellectuals and hegemonic pedagogical discourse to find the aspects of continuum and disrupt in the educational practices.